2022
DOI: 10.1007/s12094-022-02814-x
|View full text |Cite
|
Sign up to set email alerts
|

SEOM-TTCC clinical guideline in nasopharynx cancer (2021)

Abstract: Nasopharyngeal carcinoma (NPC) is distinct from other cancers of the head and neck in biology, epidemiology, histology, natural history, and response to treatment. Radiotherapy (RT) is the cornerstone of locoregional treatment of non-disseminated disease and the association of chemotherapy improves the rates of survival. In the case of metastatic disease stages, treatment requires platinum/gemcitabine-based chemotherapy and patients may achieve a long survival time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…This finding aligns with the literature, which identifies a differential age distribution of NPC in low-incidence regions compared to endemic regions. In low-incidence regions, the epidemiological pattern of NPC incidence demonstrates a bimodal distribution, with peaks observed in adolescent and young adult cohorts and a secondary increase in prevalence noted beyond the age of 65 years [10]. In stark contrast, endemic regions present a distinctly different profile, where the incidence of NPC begins to climb post-30 years of age, reaching a peak incidence within the 40-59 age group before experiencing a decline [11].…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with the literature, which identifies a differential age distribution of NPC in low-incidence regions compared to endemic regions. In low-incidence regions, the epidemiological pattern of NPC incidence demonstrates a bimodal distribution, with peaks observed in adolescent and young adult cohorts and a secondary increase in prevalence noted beyond the age of 65 years [10]. In stark contrast, endemic regions present a distinctly different profile, where the incidence of NPC begins to climb post-30 years of age, reaching a peak incidence within the 40-59 age group before experiencing a decline [11].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment methods, radiation doses, cancer staging, and radiation fields of patients with and without NPC with HNC considerably differ. Chemoradiation is the primary treatment for NPC [ 32 ], whereas surgery combined with chemoradiation is crucial for non-NPC HNC patients [ 33 ]; a study indicated that surgery and higher radiation doses to the neck may lead to damage in the carotid arteries [ 8 ]. A previous study showed that some chemotherapeutic agents, such as cisplatin and 5-Fluorouracil, may cause damage to endothelial cells and may induce local thrombosis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple international guidelines [ 17 , 18 , 19 ] are available regarding the treatment of NPC. Endemic EBV-positive non-keratinising undifferentiated NPC is both radiosensitive and chemosensitive; thus, they have formed the cornerstone of treatment for NPC patients.…”
Section: Current Diagnosis Staging and Treatment Optionsmentioning
confidence: 99%